ANALISIS PRODUKTIVITAS PEKERJAAN FINISHING PADA PROYEK TRANSIT ORIENTED DEVELOPMENT (TOD) PONDOK CINA KOTA DEPOK - Putri Aisyah Muthmainah; Afrizal Nursin (Politeknik Negeri Jakarta, 2022)
In the construction of a building project, one of the important elements in a building project is finishing work. Finishing work is a process of finishing or final completion of a building. The success of finishing work on the building depends on the success of each stage of the workers. Meanwhile, one of the factors influencing the success of a finishing work is the productivity of its workforce. This study aims to analyze productivity and what factors affect the productivity. This research uses the Relative Importance Index (RII) method, used a likert scale or a scale of 1 to 5 based on the perception of the level of interest of each respondent. Based on the results of the analysis, the performance of the project Transit Oriented Development (TOD) Pondok Cina Depok City on wall works is considered not good because the productivity index value is less than 1. Whereas the performance for floor and ceiling work is considered good because the productivity index value is more than 1. Factors that affect the productivity of finishing work are environment, work safety, education level, work experience, wages, and age. Keywords: Building, Finishing Work, Productivity.